2002
DOI: 10.1183/09031936.02.00201002
|View full text |Cite
|
Sign up to set email alerts
|

Excess incidence of asthma among Finnish cleaners employed in different industries

Abstract: The incidence and risk of asthma among female cleaners employed in different industries was explored. An increased risk of asthma has been associated with the cleaning profession, in some but not all studies.All Finnish females employed as cleaners and all those employed in administrative work were followed for asthma incidence through a record linkage in 1986-1998. An individual was defined as an "incident case of asthma" if they received rights for special reimbursement of asthma medication from the national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 17 publications
0
42
0
5
Order By: Relevance
“…For example in some Finnish studies an increased risk for asthma was observed in non-sensitising branches such as mining and quarrying (Karjalainen et al 2001), also for construction workers, welders, plumbers and asphalt roofing workers (Karjalainen et al 2002b), wood-processing industry workers (Heikkila et al 2008) and industrial cleaners (Karjalainen et al 2002a). …”
Section: Introductionmentioning
confidence: 99%
“…For example in some Finnish studies an increased risk for asthma was observed in non-sensitising branches such as mining and quarrying (Karjalainen et al 2001), also for construction workers, welders, plumbers and asphalt roofing workers (Karjalainen et al 2002b), wood-processing industry workers (Heikkila et al 2008) and industrial cleaners (Karjalainen et al 2002a). …”
Section: Introductionmentioning
confidence: 99%
“…En la actualidad, dentro del diagnóstico de asma en pacientes adultos, es importante resaltar los aspectos laborales del paciente 17 .…”
Section: Mónica Sánchez Aguilar Gabriela Betzabé Pérez-manríquez Guunclassified
“…No obstante, la mayoría de enfermedades ocupacionales pasan desapercibidas debido a una inadecuada vigilancia de los trabajadores y de las alteraciones en la salud-enfermedad por falta de pericia del personal médico que desconoce la asociación entre riesgos laborales y enfermedades ocupacionales 17 .…”
Section: Mónica Sánchez Aguilar Gabriela Betzabé Pérez-manríquez Guunclassified
See 2 more Smart Citations